Volume-based thermodynamics of organic liquids: Surface tension and the Eötvös equation - Glasser, Leslie (2021)
Many thermodynamic properties, such as entropy, lattice energy, and so forth, correlate with some function of formula volume. We here report on a recently rediscovered modified Eötvös equation which relates surface tension values to molar Gibbs surface energies, surface entropies and surface enthalpies. The resulting thermodynamic values are valuable in understanding molecular configurations of surfaces. The molar surface entropy, Δs, in what may be considered to be a Trouton surface entropy, is roughly constant at 20 J K−1 mol−1 compared with the Trouton entropy of (80–100) J K−1 mol−1 for evaporation at the boiling point of liquids.